Crises of identifying : negotiating and mediating race, gender, and disability within family and schools - Mitchell, Dymaneke D. (Educational leadership for social justice., 2013)
Although there has been an increase in literature regarding children of color with disabilities, it mainly focuses on their experiences in one social context. Crises of Identifying: Negotiating and Mediating Race, Gender, and Disability within Family and Schools includes narratives on the familial and educational experiences in public, private, and institutional educational settings of five African American adults who have disabilities associated with blindness, cerebral palsy, and speech impairment. As a deaf African American female, the author and researcher also highlights her familial and educational experiences throughout the book as a frame of analysis. This book can serve as a literary resource to academics and educational programs and/or institutions as well as an informational guide to parents, teachers, administrators, and paraprofessionals/caregivers of children with disabilities regarding the significance of leadership, advocacy, activism, and identification development within familial and educational contexts on the experiences of children including the impact of complex dynamics that exist within and between families and schools.Hopefully, this book will provide parents, teachers, administrators, and paraprofessionals with an understanding and comprehension of complexities concerning disability, gender, and race within family and schools including their association with crises of identifying, essentialist discourses, as well as power and privilege dynamics. This book consists of nine chapters which are organized into three parts. Part I focuses on background, rationale, theoretical and methodological underpinnings of the research this book is based on. Part II introduces the reader to the narratives of five African Americans with disabilities. Each narrative provides insights into the lived experiences and leadership qualities of two males and three females. Part III presents the concluding chapters of the book and highlights the significance of this research for the educational field including disability studies, teacher education programs, and special education.